Hubungan Kebermaknaan Hidup dengan Resiliensi pada Remaja di Panti Asuhan Bani Adam-As Medan - Fitri Adeinsani Effendi; Endang Haryati (Mahesa Research Center, 2022)
This study aims to find the correlation between the meaning of life and resilience in adolescents at the Bani Adam-As orphanage. This study uses a quantitative approach. The subjects in this study were orphanage adolescents aged 16-18 years. This study used purposive sampling as the sampling technique, which technique is based on specific considerations, so the sample amount to 52 adolescents. The hypothesis in this study is that there is a positive correlation between the meaning of life and resilience. The data collection technique used the Likert scale. Data analysis using product moment analysis. Based on the analysis that has been done, there is a coefficient value (Rxy) of 0.693 with p = 0.000 <0.050. The result shows that the hypothesis in this study is